2004
DOI: 10.4049/jimmunol.172.9.5544
|View full text |Cite
|
Sign up to set email alerts
|

Allelic Exclusion at the TCRδ Locus and Commitment to γδ Lineage: Different Modalities Apply to Distinct Human γδ Subsets

Abstract: Expression of a β-chain, as a pre-TCR, in T cell precursors prevents further rearrangements on the alternate β allele through a strict allelic exclusion process and enables precursors to undergo differentiation. However, whether allelic exclusion applies to the TCRδ locus is unknown and the role of the γδ TCR in γδ lineage commitment is still unclear. Through the analysis of the rearrangement status of the TCRγ, δ, and β loci in human γδ T cell clones, expressing either the TCR Vδ1 or Vδ2 variable regions, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 47 publications
2
12
0
2
Order By: Relevance
“…However our data indicates that both TCRγ alleles rearrange in the majority of T cells, in agreement with the prior published data (38). Other evidence also suggests that TCRγ rearranges prior to the cell fate determination and, therefore, prior to thymic selection (18, 36).…”
Section: Discussionsupporting
confidence: 94%
“…However our data indicates that both TCRγ alleles rearrange in the majority of T cells, in agreement with the prior published data (38). Other evidence also suggests that TCRγ rearranges prior to the cell fate determination and, therefore, prior to thymic selection (18, 36).…”
Section: Discussionsupporting
confidence: 94%
“…We did find extensive D3 J␤ rearrangements in human ␥␦ cells (data not shown), indicating that early on, at least part of the TCR␤ locus was accessible to the recombination machinery. Our data are consistent with those of Couedel et al (53) who showed that cloned peripheral blood ␥␦ T cells contained a low percentage of complete V3 DJ␤ rearrangements. Second, and more importantly, the few complete ␤ rearrangements detected were predominately out-of-frame (Table III), suggesting an instructional role for the pre-TCR in diversion away from the ␥␦ lineage.…”
Section: Discussionsupporting
confidence: 83%
“…In humans, the earliest thymic progenitors (CD34+CD1a−) have a rearranged Tcrd locus, while the Tcrb locus remains in germline configuration [26]. Additionally, partial allelic exclusion is evident at the Tcrg locus [27], indicating that γ chains are pairing with preexisting δ chains. …”
Section: γ δ T Cell Developmentmentioning
confidence: 99%